Definition of Uveitis Refractory to Treatment: A Systematic Review in the Absence of a Consensus. (2nd January 2022) - Valenzuela, Rodrigo A.; Flores, Iván; Pujol, Myriam; Llanos, Carolina; Carreño, Ester; Rada, Gabriel; Herbort, Carl P.; Cuitino, Loreto; Urzua, Cristhian A.
ABSTRACT: Purpose: To evaluate the different definition of refractoriness in uveitis in the literature. Methods: We systematically searched the literature in order to identify definitions of refractory noninfectious uveitis in adult patients. A search strategy in the databases of MEDLINE and Scopus was used to find articles published between January 2005 and October 2018. Results: Definitions of corticosteroids-refractoriness were related to two main concepts: persistence of inflammation despite the use of corticosteroid and recurrences above a dosage threshold. In terms of immunomodulatory therapy and biologic agents, we observed a great variety of definitions: persistence of inflammation, number of attacks, side effects or complications, symptoms, and best-corrected visual acuity. Conclusions: The results of this systematic review demonstrate the current lack of consensus on the definition for refractory uveitis, regardless of the treatment being used and revealed a new terminology based on a comprehensive and operational definition for each specific category of refractoriness.